1973
DOI: 10.1192/bjp.123.6.643
|View full text |Cite
|
Sign up to set email alerts
|

Language Structure and Predictability in Overinclusive Patients

Abstract: Deviant language behaviour is the primary basis for the clinical inference of thought disorder. Bleuler (1950), for example, emphasizes loose associations and disjointed utterances. Mayer-Gross, Slater, and Roth (1960) state that thought disorder is indicated by such conversation characteristics as ‘woolly vagueness', in-consequential following of side issues, direction by alliteration, analogies or clang associations, and the use of words out of context. However, psychological studies have typically used meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…1991). Both these measures were relatively specific to patients who were characterized clinically as being thought disordered (measures using Cloze analysis: Hart and Payne 1973; Manschreck et al. 1979; measures using the Type:Token ratio: Allen 1983; Manschreck et al.…”
Section: Descriptions Of Language In Schizophreniamentioning
confidence: 99%
“…1991). Both these measures were relatively specific to patients who were characterized clinically as being thought disordered (measures using Cloze analysis: Hart and Payne 1973; Manschreck et al. 1979; measures using the Type:Token ratio: Allen 1983; Manschreck et al.…”
Section: Descriptions Of Language In Schizophreniamentioning
confidence: 99%
“…Moreover, when more context was provided, it proved easier to predict upcoming words in controls’ speech, but harder to make such predictions in patients’ speech (Salzinger, Pisoni, Portnoy, & Feldman, 1970; Salzinger, Portnoy, & Feldman, 1979). Later studies suggested that such unpredictability was most characteristic of speech produced by patients who had been clinically characterized as thought disordered (Hart & Payne, 1973; Manschreck, Maher, Rucklos, & White, 1979). …”
Section: Introductionmentioning
confidence: 99%
“…However, that is not relevant to our main hypothesis, which is 275 Downloaded by [Temple University Libraries] at 04:59 04 June 2016 that, whatever brings it about, the trend towards better control over regression will manifest itself in the linguistic style of the patient. Moreover, previous research on stylistic effects of medication has not demonstrated reliable effects of medication on style (Feldstein & Jaffe 1963, Hart & Payne 1973, Johnstone et al 1978.…”
Section: Discussionmentioning
confidence: 93%
“…As regards the effects of medication on style, findings are generally negative. Feldstein & Jaffe (1963), Hart & Payne (1973), and Johnstone, Crow, Frith, Carney, & Price (1978), among others, found no effects, although Hart & Payne (1973) also noted some unexpected ones. Positive findings have been noted with respect to communicative ability rather than linguistic style.…”
Section: Rolf Sandell and Kerstin L1pschi3tzmentioning
confidence: 91%